Comparisons between chest trunk mobilization with sustained maximum inspiration and ﬂow incentive spirometry on chest expansion, respiratory muscle strength, and functional exercise capacity in patients undergoing video-assisted thoracoscopic surgery - Wattanananont, Khanistha; Buranapuntalug, Sasipa; Laohathai, Sira (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Chest trunk mobilization with sustained maximum inspiration (SMI) and ﬂow incentive spirometry (ﬂow IS) are breathing techniques that mostly apply to patients undergoing video-assisted thoracoscopic surgery (VATS). The purpose of this study was to determine the eﬀects of chest trunk mobilization with SMI and ﬂow IS on chest expansion, respiratory muscle strength, and functional exercise capacity in patients undergoing VATS.Methods. Sixty VATS patients were randomly allocated into chest trunk mobilization with SMI (n = 30) and ﬂow IS (n = 30) groups. Each group performed a physical therapy program preoperatively and 4 days post-operatively. Chest expansion at upper, middle, and lower levels, inspiratory and expiratory muscle strengths, and functional exercise capacity were deter-mined at pre- and post-VATS.Results. In both groups, chest expansion at all levels, expiratory muscle strength, and distance of the 6MWT signiﬁcantly increased (p < 0.05) post-operatively compared to pre-operative assessments, although there was no signiﬁcant diﬀerence between groups. In addition, inspiratory muscle strength signiﬁcantly improved from baseline in both groups (p < 0.05), but the ﬂow IS group showed a greater increase than the chest trunk mobilization with the SMI group (78.17 ± 24.16 and 65.57 ± 20.39 cm H2O, respectively, p < 0.05).Conclusions. Chest trunk mobilization with SMI and ﬂow IS can improve chest expansion at all levels, as well as respiratory muscle strength and the distance of the 6MWT. However, ﬂow IS enhances inspiratory muscle strength to a greater extent than chest trunk mobilization with SMI. Ultimately, both techniques can be applied eﬀectively in patients undergoing VATS.
Keywords: video-assisted thoracoscopic surgery; respiratory muscle training; breathing exercises; physical therapy; incentive spirometer